The secret life ferns - Jensen, Lawrence; Chung, Andrew (New Zealand : ETI ; Dr. Lawrence Jensen, 1999)
Three diemnsional animations take you in and around reproductive structures such as the sorus, sporangium, antheridium and archegonium. You can see dynamic events such as spore formation, spore release, prothallus formation, sperm release, fertilisation and embryo growth
Title from title screen
Editors, Richard Smith ; animation, Andrew Chung ; camera, Graeme Henderson, Richard Smith
Narrator: Richard Smith
Keywords: Ferns -- Anatomy; Ferns